Learners’ Perception of National Open University of Nigeria’s Online Assessment Courseware Usability’ - Osuji, U.S.A (West African Journal of Open and Flexible Learning, 2014)
Computer-based learning and assessment have become very popular throughout the world. This is as a result of the acceptance of Open and Distance Learning (ODL) as an effective mode of education. It has been proved to be cost effective, aside the fact that they are implemented for its various advantages and capabilities. Computer- based applications have been increasingly developed not only for teaching and learning in ODL but also for use in the normal classroom setting. It has also been proved beneficial for students with learning disabilities including slow learners. One of the examples of the computer- based applications is the online assessment used in the National Open University of Nigeria (NOUN). This study is aimed at finding out the perception of the learners in NOUN in relation to the usability of the online assessment courseware being used for their assessment. An instrument termed Learners’ Perception of Online Assessment Courseware Usability (LPOACU), was developed and administered on 200 level students from Owerri and Umudike centres of NOUN. A total of 124 respondents returned their instruments for analysis. The result shows that learners have positive attitude and perception towards the usability properties of the assessment courseware.